Syntheses and Crystal Structure of Ce(IV) Complex Containing 4-Heterocyclic Acylpyrazolone - Zhao1, C.X.; Ding2, Y.J.; Yuan1, T.T.; Wanyan1, D.Y.; Guo1, Y.J.; Hu1, Z.Z.; Li1, X. (Asian Journal of Chemistry, 2014)
A novel Ce complex of 4-acylpyrazolones of formula [Ce(CPTP)4] (C6H5CH3)3 (HCPTP = 1-(4-chlorophenyl)-3-phenyl-4-thenoyl-1H-pyrazol-5-ol) has been synthesized and characterized. It crystallizes in the triclinic space group P-1 with a = 12.9770(12) Å, b = 16.7877(15) Å, c = 21.8362(19) Å; a = 105.5250(10)º, b = 93.389(2)º, g = 99.209(2)º, V = 4498.4(7) Å3, C101H72N8O8S4CeCl4, Mr = 1935.87, Z = 2, Dc = 1.429 g/cm3, m = 0.781 mm-1, F(000) = 1976, R = 0.0312 and wR = 0.0696 for 16643 observed reflections with I > 2s(I). The complex is mononuclear. In air and solution stable compounds containing an eight-coordinated Ce(IV) center in a distorted dodecahedral configuration, the average Ce-O bond length is 2.3351(14) Å.